(untitled) (Journal of Information Technologies in Education (ITE), 2015)
The approaches are analyzed and the development of a generalized functional model of the dual content of training of future engineers-teachers of computer type is implemented in the article.We propose a class of functional models of the dual content of professional training based on the timing of psychological, pedagogical and engineering component of the professional training. As the main synchronizers in the functional models of dual content two professionally designed psycho-pedagogical disciplines "Didactic bases of vocational education" and "Methods of vocational training" were selected. Functional models which were selected and proposed are represented by the functional linear model of the dual content of professional training for the first stage of integration, by functional concentric model (after the composition of methods) of dual content of professional training of future engineers-teachers for the first stage, the concentric functional model of the dual content of professional training (after the content of methodology) for the second stage, the functional model of adaptive dual control of the content of professional training of future engineersteachers for the third stage of implementation of the dual content of the vocational training. The generalized functional model of the dual content of professional training of future engineersteachers of computer profile will let implement the process of learning of dual content. Using this model will facilitate the formation of professional dual competences of future engineer-teacher of computer profile; optimization of the educational process; formation of professional orientation of training.